Incorporating Blood Flow in Nerve Injury and Regeneration Assessment - Yeoh, Stewart; Warner, Wesley S.; Merchant, Samer S.; Hsu, Edward W.; Agoston, Denes v.; Mahan, Mark A. (Frontiers in Surgery, 2022)
Peripheral nerve injury is a significant public health challenge, with limited treatment options and potential lifelong impact on function. Blood vessels are an intrinsic part of nerve anatomy, and nerve regeneration is dependent on adequate vascular perfusion for metabolic demands, appropriate signaling and growth factors, and structural scaffolding for Schwann cell and axonal migration and repair. However, the established nerve injury classification paradigm proposed by Sydney Sunderland in 1951 is based solely on hierarchical disruption to gross anatomical nerve structures and lacks further information regarding the state of cellular, metabolic, or inflammatory processes that are critical in determining regenerative outcomes. This review covers the anatomical structure of nerve-associated vasculature and describes the biological processes that makes these vessels critical to successful end-organ reinnervation after severe nerve injuries. We then propose a theoretical framework that incorporates measurements of blood vessel perfusion and inflammation to unify perspectives on all mechanisms of nerve injury.